Enhancing Breastfeeding Mothers' Knowledge and Expertise in Lactation Management in Menayu Village as a Child-Friendly Village - Rohmayanti, Rohmayanti (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2023)
Menayu Village, Muntilan District, Magelang, became the pilot village as a Child Friendly Village (DLA). However, it does not meet the requirements as a DLA, especially in fulfilling children's rights in the cluster of children's basic health rights, such as the coverage of exclusive breastfeeding, which does not match the national percentage, there are health cadres, but they do not focus on lactation issues. The purpose of this activity is to provide lactation management training to increase knowledge and skills among breastfeeding mothers. The method used is the Participatory Rural Appraisal (PRA) model, which was carried out for three months in Menayu Village, the number of participants in this activity was 15-20 breastfeeding mothers and health cadres. The activity was carried out through the first stage, namely program socialization involving the village head, village midwife, and health cadres in the village. The second stage is counseling and training in lactation management skills, including the importance of exclusive breastfeeding, problems that occur during breastfeeding, skills in the form of oxytocin massage, how to express breast milk, and how to store breast milk. Finally, the assistance stage is followed by monitoring and evaluation. The results of lactation management training activities for breastfeeding mothers can increase their knowledge and skills in lactation management. This activity is an effort to fulfill children's rights in an effort to fulfill children's basic health rights in the process of growth and development in child-friendly villages in Menayu Village.